Extreme measures - Flynn, Vince (New York : Pocket Books, 2009)
The CIA has detected and intercepted two terrorist cells, but a third is feared to be on the loose. Led by a dangerous mastermind obsessed with becoming the leader of al-Qaeda, this determined and terrifying group is about to descend on America. Mitch Rapp needs the best on this assignment, and Nash, who has served his government honorably for sixteen years--first as an officer in the Marine Corps and then as an operative in an elite counterterrorism team run by Rapp--is his choice. But on this assignment Rapp and his protege may have met their match.
Originally published: New York : Atria Books, 2008.
Keywords: Rapp, Mitch (Fictitious character) -- Fiction; Terrorism -- Prevention -- Fiction; Intelligence officers -- Fiction; Political fiction; Suspense fiction